(untitled) (Periphērica, 2020)
This article connects the dehistoricized pasts in Pablo Berger’s film Blancanieves(2014) and Jesús Carrasco’s novel Intemperie (2013) to the present economic, cultural and ecological crises occurring within Spain and at a worldwide level. Both film and novel can be linked to contemporary anxieties: Blancanievesto an image-obsessed society of consumer abundance facing a present and future of increasing scarcity; Intemperie to the threat of environmental collapse. Their invoking of the past suggests that economic and ecological strife bring back the specter of past violence and misery, unleashing the negative affects that pervade an individualist society based on competition and inequality. The aesthetics of verbal silence in both texts encourage a raw affective engagement and are analyzed here as a critical response to the individualist culture at the root of current crises, proposing alternative ethics of empathy and intersubjectivity. The social-political projects underlying these texts can thus be related to the 15M movement in Spain. They construct similar landscapes of anguish and hope, and they confront the same destructive ethos of fear, envy and domination that operate simultaneously on a societal level and within the self.